(untitled) (Fiep Bulletin - online, 2011)
This study has the purpose of searching the understanding about ethics and morals and its relationship with school, and, by extension, the physical education classes. It intends to provoke the reflection about social relationships and development of ethical skills in physical education classes, as well. It also intends to emphasize the importance of the incitement from school to form citizenship and incite responsibility from the educational system and professional people of this area, to articulate, to advertise and encourage physical education, in a perspective of recognition, based on important and relevant discussions and documents, besides the necessity of implanting political ethics, just as fast as possible, which could provide better learning, and in fact, offer equality of opportunities and living experiences on relationships built at school. To the physical education professional is delegated the arousing of people which one works with, to the real exercise of citizenship, to conduce social changes and forming human beings, as integral as possible.